(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2016)
The aim of the paper is to reflect on the existence of sustainable economic development in Nicaragua in the period between 2010 and 2015. The methodology consisted in a descriptive, explanatory and correlational analysis of the evolution Public Policy and the Environment in Nicaragua. The results obtained confirm these reasoning implicit assumptions about the expected relationship between Public Policy and the Environment, and there have been some weaknesses in both areas as engines of development. The sustainability of development in Nicaragua is possible through the development and effective implementation of public policies and the harmonization with the environment, because Nicaragua has environmental potential that serves as the basis for production, the key lies in the optimal use of the building through public policies that seek efficiency and equity. REICE Vol.3(6) 2015: 158-179